2022
DOI: 10.3389/fgene.2022.1037190
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of growth factors in osteonecrosis of the femoral head

Abstract: Osteonecrosis of the femoral head (ONFH) is a potentially disabling orthopedic condition that requires total hip arthroplasty in most late-stage cases. However, mechanisms underlying the development of ONFH remain unknown, and the therapeutic strategies remain limited. Growth factors play a crucial role in different physiological processes, including cell proliferation, invasion, metabolism, apoptosis, and stem cell differentiation. Recent studies have reported that polymorphisms of growth factor-related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 178 publications
0
1
0
Order By: Relevance
“…[83,84] Due to the development of surgery and imaging technology, ARCO developed a new classification of early (pre-collapse) ONFH in 2022. [85] The necrotic lesions were divided into 3 types: type 1 was a small lesion, and the lateral necrotic edge was located inside the vertex of the femoral head; type 2 was a medium-sized lesion, and the lateral necrosis edge was located between the apex of the femoral head and the lateral edge of the acetabulum. And type 3 is a large lesion, extending to the outer edge of the acetabulum.…”
Section: Early Onfh and Core Decompression Combined With Autologous S...mentioning
confidence: 99%
“…[83,84] Due to the development of surgery and imaging technology, ARCO developed a new classification of early (pre-collapse) ONFH in 2022. [85] The necrotic lesions were divided into 3 types: type 1 was a small lesion, and the lateral necrotic edge was located inside the vertex of the femoral head; type 2 was a medium-sized lesion, and the lateral necrosis edge was located between the apex of the femoral head and the lateral edge of the acetabulum. And type 3 is a large lesion, extending to the outer edge of the acetabulum.…”
Section: Early Onfh and Core Decompression Combined With Autologous S...mentioning
confidence: 99%
“…It has been showed that critical genes of Wnt/β-catenin pathway play important roles in fat accumulation of the lesion bone marrow cavity of ONFH 5 , 6 , but it has rarely been reported that the effects of paired interactions of multiple variants in Wnt/β-catenin pathway genes on ONFH occurrence and development. The relevant reports suggest that chronic corticosteroid use and excessive alcohol consumption are the two main environmental risk factors of ONFH, and multiple genes are associated with ONFH risk 7 , 8 . In particular, some evidences revealed that the imbalance between osteogenesis and adipogenesis regulated by Wnt/β-catenin pathway played essential roles in the development of ONFH 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%